Convex Enclosures for Constrained Reachability Tubes. Issue 1 (2019) - Villanueva, Mario E.; Feng, Xuhui; Paulen, Radoslav; Chachuat, Benoît; Houska, Boris
Abstract: This paper is concerned with computing enclosures for the constrained reachable set of uncertain nonlinear dynamic systems. Our main contribution is a nontrivial extension of the generalized differential inequality, proposed in Villanueva et al. (2015), for the case that an a priori enclosure, of the reachable set is available. A practical implementation is worked out in detail for the case of ellipsoidal enclosures. The applicability of the proposed method is illustrated using a Lotka-Volterra system, for which a nonlinear solution invariant is known.